2015
DOI: 10.1152/ajpheart.00378.2015
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Ets-1 attenuates epidermal growth factor-dependent collagen loss in human carotid plaque smooth muscle cells

Abstract: Rao VH, Rai V, Stoupa S, Agrawal DK. Blockade of Ets-1 attenuates epidermal growth factor-dependent collagen loss in human carotid plaque smooth muscle cells. Am J Physiol Heart Circ Physiol 309: H1075-H1086, 2015. First published August 7, 2015 doi:10.1152/ajpheart.00378.2015.-Although degradation of extracellular matrix by matrix metalloproteinases (MMPs) is thought to be involved in symptomatic (S) carotid plaques in atherosclerosis, the mechanisms of MMP expression are poorly understood. Here, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…In our studies, TREM-1 blocking experiments with either TREM-1 antibody or TREM-1 fusion protein (rTREM-1/Fc) significantly decreased the expression of both MMP-1 and MMP-9 and increased collagen genes. Recently, we reported [8] increased expression of MMPs and decreased expression of collagen genes in VSMCs isolated from S plaques supporting their role in plaque stability [35]. Other studies have suggested the involvement of collagen in the stability of atherosclerotic plaques [8, 36, 37].…”
Section: Discussionmentioning
confidence: 72%
“…In our studies, TREM-1 blocking experiments with either TREM-1 antibody or TREM-1 fusion protein (rTREM-1/Fc) significantly decreased the expression of both MMP-1 and MMP-9 and increased collagen genes. Recently, we reported [8] increased expression of MMPs and decreased expression of collagen genes in VSMCs isolated from S plaques supporting their role in plaque stability [35]. Other studies have suggested the involvement of collagen in the stability of atherosclerotic plaques [8, 36, 37].…”
Section: Discussionmentioning
confidence: 72%
“…Thinning of the fibrous cap is mediated by the degradation of the collagen content of the extracellular matrix by the matrix metalloproteinases (MMPs) resulting in plaque rupture and ischemic events (Butoi et al 2016;Newby 2015;Rao et al 2015). Further, it has also been documented that S100A8…”
mentioning
confidence: 99%
“…MMPs are secreted from synovial fibroblasts and directly responsible for matrix breakdown and promoting progression of TMJOA 36e38 . MMP1 and MMP9 expression was reported to be induced by Ets-1 activation in smooth muscle cells 39 and human ovarian carcinoma 40 . Likewise, our findings have shown that expressions of MMP1 and MMP9 were reduced by miRNA221-3p through targeting Ets-1 in TMJOA synovial fibroblasts.…”
Section: Discussionmentioning
confidence: 99%